Histopathologic Spectrum of Findings Associated With Tattoos: Multicenter Study Series of 230 Cases. (August 2021) - Portilla Maya, Nataly; Kempf, Werner; Perez Muñoz, Noelia; Rodríguez-Martínez, Paula; Posada, Rodolfo; Fernández-Figueras, María Teresa
Abstract : Importance: Reactions to tattoo may simulate common dermatosis or skin neoplasms. Histopathology allows diagnosis and helps determining the level and degree of inflammation associated, consequently orientating treatment. Objective: To describe the histological features found in biopsies of cutaneous reactions to tattoo. Design: This study was designed as a multicenter case series. Setting: All consecutive histopathological samples of tattoos referred from 1992 to 2019 to the Hospital General de Catalunya, Hospital Germans Trias i Pujol, and a private practice, all in Barcelona, Spain, and from the Kempf und Pfaltz Histologische Diagnostik in Zurich, Switzerland were retrieved from the files. Participants and Exposure: The inclusion criteria were all cosmetic/permanent makeup, artistic/professional, and traumatic tattoos associated with either inflammatory reactions alone and/or with tumors and/or infections. Exclusion criteria were cases without any associated pathologic finding in the place of the ink, amalgam tattoos, and medical or temporary tattoos. Main Outcomes and Measures: In all patients, clinical features (age, sex, location, tattoo color, and presentation) were recorded. Histological features evaluated included ink color, associated tumors or infections, and inflammatory reaction pattern. Inflammation was graded in low to moderate or severe. Results: From 477 biopsies diagnosed as tattoos, 230 cases from 226 patients met the inclusion criteria. Samples corresponded to 107 male and 120 female subjects and 3 of unknown gender. Median age was 39 years (ranging from 9 to 84 years). Fifty-three samples were referred from centers in Spain and 177 from the center in Switzerland. The series was analyzed in 2 parts: tattoos associated only with inflammatory reactions (117/230) and tattoos associated with tumors or infections (113/230). The most common form of inflammatory pattern associated with tattoo was the fibrosing reaction (79/117, 68%), followed by granulomatous reaction (56/117, 48%), lichenoid reaction (33/117, 28%), epithelial hyperplasia (28/117, 24%), pseudolymphoma (27/117, 23%) and spongiotic reaction (27/117, 23%). Combined features of 2 or more types of inflammatory patterns were seen in 64% cases. Conclusions and Relevance: Our series confirms that cutaneous reactions to tattoos are polymorphous. Inflammation tends to present with combined patterns. Infections are tending to decline, and pathologic findings are not specific to ink color or clinical features. Abstract : Supplemental Digital Content is Available in the Text.